The impact of SafeCare® Dads to Kids program on father maltreatment risk and involvement: Outcomes and lessons learned from an efficacy trial. (September 2018) - Self-Brown, Shannon; Osborne, Melissa C.; Boyd, Clinton; DeVeausse Brown, Natasha; Rostad, Whitney; Patterson, Alexandria; Baker, Evander; Thomas, Akilah; McAdam, Elizabeth M.; Jackson, Matt; Glasheen, Theresa L.; Lai, Betty
Abstract: Child Maltreatment (CM) is a public health problem, and experts recommend parent training programs as a prevention method. Few programs target fathers, even though male caregivers are involved as perpetrators in approximately 45% of substantiated CM cases. This study examines the efficacy of an adapted version of SafeCare (Dad2K) with marginalized fathers. Participants include a convenience sample of fathers with children ages 2–5 years. Fathers (n=99) were randomized to an 1) intervention group (SafeCare Dad2K) or to a 2) comparison group (receiving parenting information in the mail). Quantitative data were collected at baseline, post-intervention (7-weeks post-baseline), and 3-months post-intervention. Qualitative data (semi-structured interviews) were collected from 11 intervention father completers following the second quantitative data collection timepoint. Multi-level modeling results indicated no statistically significant time-by-treatment findings for father involvement (b=0.03, 95% confidence interval [CI]: −0.03, 0.08, p=0.38), total corporal punishment (b=-0.03, 95% CI: −0.47, 0.41, p=0.89), or neglect (b=-0.13, 95% CI: −1.93, 1.68, p=0.89). Qualitative findings indicated that Dad2K completers exhibited positive knowledge and behavioral change related to parenting. Study limitations, lessons learned from this formative work, and recommendations for future research are discussed.